PENGARUH KEBIJAKAN PEMERINTAH TERHADAP KINERJA PERUSAHAAN UKM - Wihalminus Sombolayuk (Faculty of Economics dan Business, Atma Jaya Makassar University, 2023)
This study aims to analyze the direct influence of government policies on the performance of SMEs. This research is a quantitative study using deductive methods. The number of samples is 180 SME companies in the food and beverage industry as the unit of analysis and analysis, regression with the help of Amos software. The results of this study indicate that government policies have a direct positive effect on the performance of SME companies. The more quality government policies in developing SME companies will further improve the performance of SME companies. The novelty of this study is that policy orders through production development programs, marketing, financial human resources, and institutional strengthening of SME companies have a direct and significant positive effect on the performance of SME companies.